Evolving trends in epidemiology and natural history of cardiac amyloidosis: 30-year experience from a tertiary referral center for cardiomyopathies - Aldostefano Porcari; Valentina Allegro; Riccardo Saro; Guerino Giuseppe Varrà; Linda Pagura; Maddalena Rossi; Andrea Lalario; Francesca Longo; Renata Korcova; Matteo Dal Ferro; Andrea Perkan; Franca Dore; et al. (Frontiers in Cardiovascular Medicine, 2022)
ObjectiveNatural history of cardiac amyloidosis (CA) is poorly understood. We aimed to examine the changing mortality of different types of CA over a 30-year period.Patients and methodsConsecutive patients included in the “Trieste CA Registry” from January 1, 1990 through December 31, 2021 were divided into a historical cohort (diagnosed before 2016) and a contemporary cohort (diagnosed after 2016). Light chain (AL), transthyretin (ATTR) and other forms of CA were defined according to international recommendations. The primary and secondary outcome measures were all-cause mortality and cardiac death, respectively.ResultsWe enrolled 182 patients: 47.3% AL-CA, 44.5% ATTR-CA, 8.2% other etiologies. The number of patients diagnosed with AL and ATTR-CA progressively increased over time, mostly ATTR-CA patients (from 21% before 2016 to 67% after 2016) diagnosed non-invasively. The more consistent increase in event-rate was observed in the long-term (after 50 months) in ATTR-CA compared to the early increase in mortality in AL-CA. In the contemporary cohort, during a median follow up of 16 [4–30] months, ATTR-CA was associated with improved overall and cardiac survival compared to AL-CA. At multivariable analysis, ATTR-CA (HR 0.42, p = 0.03), eGFR (HR 0.98, p = 0.033) and ACE-inhibitor therapy (HR 0.24, p < 0.001) predicted overall survival in the contemporary cohort.ConclusionIncidence and prevalence rates of ATTR-CA and, to a less extent, of AL-CA have been increasing over time, with significant improvements in 2-year survival of ATTR-CA patients from the contemporary cohort. Reaching an early diagnosis and starting disease-modifying treatments will improve long-term survival in CA.